Ang pangit na itik - Andersen, Hans Christian 1805-1875.; Langley, Glynis; Fryer, David (Manchester [England} World International Pub., 1980)
The new duckling is scorned by everyone because he is different but after a lonely winter he discovers he has grown into a beautiful swan.
Keywords: Fairy tales